Association of Procalcitonin Level with the Severity of Pneumonia in Children under 5 Years of Age: A Prospective Cohort Study - P Ananya; SS Kalyanshettar; Trimal P Kulkarni; Mallanagouda M Patil (Journal of Clinical and Diagnostic Research)
Introduction: Community Acquired Pneumonia (CAP) is a significant global health problem, with notable variations in incidence, causative pathogens, and outcomes across different regions and populations. Procalcitonin (PCT) has been established as a marker of bacterial infection to differentiate septic from other infections in paediatric patients. Aim: To evaluate the severity of pneumonia in children under 5 years of age according to the parameters of Acute Illness Observation Scale (AIOS) and also to study its association with serum PCT level. Materials and Methods: The present prospective cohort study was conducted in the Paediatric Intensive Care Unit (ICU) of BLDE deemed to be university, Shri BM Patil Medical College, Vijayapura, Karnataka, India, between March 2023 and October 2024. A total of 51 children aged between 2 to 59 months were included in the study who presented with fever, cough, and rapid breathing, along with any of the following symptoms: chest in drawing in a calm child, stridor, grunting, lethargy, convulsions, and decreased appetite. The AIOS was used to assess the children on Day 1, Day 2, and Day 5 of admission. On admission, venous blood was drawn and processed for serum PCT. The data collected was entered into a Microsoft Excel spreadsheet and analysed using Statistical Package for the Social Sciences (SPSS), Version 20. Results: The age in the study group ranged from two months to 59 months, among them the majority were in the age group of 12 months- 5 years, i.e., 27 (52.9%) patients, followed by 24 (47.1%) patients in the age group of <12 months. A total of 33 (64.7%) patients were male children and 18 (35.3%) patients were female. It was found that 29 (56.9%) patients had moderate AIOS on day 1 and then 32 (62.7%) patients had mild AIOS on day 2 followed by 37 (72.5%) patients had mild AIOS on day 5. It was found that there was a significant association between AIOS score and PCT level and also with PCT and C-reactive Protein (CRP) level (p-value <0.05). Conclusion: Both the AIOS and serum PCT levels demonstrate a strong ability to detect the severity level and determine clinical outcomes in paediatric patients with CAP.